To fight tuberculosis, fund basic research - Grundner, Christoph (PLoS Biol, 2018)
Tuberculosis (TB) is now the leading cause of death from infectious disease. On September 26, 2018, the United Nations (UN) General Assembly holds its first high-level meeting on TB, a once-in-a-lifetime chance to commit governments around the world to redouble their TB control efforts. Here I share impressions from a preparatory meeting at the UN in June and make the case for basic research as a central component of any future TB control strategy. The pathogen that causes TB, Mycobacterium tuberculosis, is still largely a mystery. But if we do not understand the basic, fundamental workings of the pathogen, we cannot hope to develop 21st century interventions for the disease.